Analisis Bibliometrik Perkembangan Penelitian Terkait Integrated Sustainable Waste Management (Iswm) Tahun 2020-2024 Menggunakan Vosviewer - Agum Muladi; Samsul Hadi (LPPM, Institut Teknologi dan Kesehatan Aspirasi, 2024)
This bibliometric research focuses on mapping research with a database of research articles from the sciencedirect website. This research was conducted to determine the development of research in the field of waste management, especially integrated sustainable waste management. Data collection was carried out based on the sciencedirect database with the keyword